Rancang Bangun Digital Librarypada Sekolah Tinggi Teknologi Pagaralam Menggunakan PHP Dan Mysql - Alfis Arif (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
Design of Digital Library at the College of Technology Pagaralam using PHP and MySQL (2014 ) Thesis . Program Information Engineering College of Technology Pagaralam, in March 2014. The purpose of the research is to create a Digital Library at the College of Technology Pagaralam using PHP and MySQL and System Development method used is the method of Web Engineering with the stages: Customer Communication,Planning ,Modelling , Construction and Deployment . By Making Digital Library at the College of Technology Pagaralam using PHP and MySQL enabling acquired the website dynamic and easily updated anytime. Besides, this website can also be one of the means for the College of Technology Pagaralam to provide a cheaper alternative media for Students, Faculty, and Society.